2014
DOI: 10.1245/s10434-014-3885-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approaches to Advanced Gallbladder Cancer

Abstract: Surgery may not be indicated for patients with multiple liver metastasis, dissemination, Binf3, or visible para-aortic LN metastasis. Furthermore, it is important to achieve R0 surgery in cases of GBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In this study, we analyzed the impact of CBD resection in T3 patients and found that patients with and without CBD resection had similar OS. CBD resection did not yield a higher lymph node count and was not associated with an improved survival [10]. This result was also confirmed by Gani in a study involving 449 GBC patients [50].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In this study, we analyzed the impact of CBD resection in T3 patients and found that patients with and without CBD resection had similar OS. CBD resection did not yield a higher lymph node count and was not associated with an improved survival [10]. This result was also confirmed by Gani in a study involving 449 GBC patients [50].…”
Section: Discussionmentioning
confidence: 67%
“…Curative resection may be the only available method to cure patients presenting with GBC [18]. It has been widely considered a critical factor influencing the prognosis of GBC in many reports [10,1922]. Curative resection should be performed according to TNM staging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional lymph node dissection is indispensable and invaluable for the accurate staging of gallbladder cancer. 3 4 The extent of resection in gallbladder cancer is usually determined by the pre- and intraoperative assessment of the nature and extent of the tumor invasion. According to the National Comprehensive Cancer Network (NCCN) guidelines, 5 simple cholecystectomy is considered appropriate to treat T1a gallbladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Radical resection is currently the main treatment option for GBCs[ 4 , 5 ]. Unfortunately, due to the nonspecific symptoms and highly invasive character of GBC, only a minority of patients are candidates for curative resection at the time of diagnosis[ 4 , 6 ]. In current, the commonly used TNM staging system is inadequate to predict accurate clinical outcomes of GBCs.…”
Section: Introductionmentioning
confidence: 99%